Concept and development of an interactive tool for trial recruitment planning and management - Spies, R.; Siegfried, N.; Myers-Franchi, Bronwyn; Grobbelaar, S.S. (BMC, 2021)
Background: Predicting and monitoring recruitment in large, complex trials is essential to ensure appropriate resource management and budgeting. In a novel partnership between clinical trial investigators of the South African Medical Research Council and industrial engineers from the Stellenbosch University Health Systems Engineering and Innovation Hub, we developed a trial recruitment tool (TRT). The objective of the tool is to serve as a computerised decisions-support system to aid the planning and management phases of the trial recruitment process.